Between Two Epochs - Fadel, Maurice (Poznańskie Studia Slawistyczne, 2019)
This review is a short presentation and an analysis of the book България – страна на розите, published in 2018. The book consists of three parts – a phototypical copy of the first Polish edition of the collective book from 1938, a translation of this edition into Bulgarian language with biographies of the authors of the texts and several studies, dedicated to Metodi Konstantinov (the 1938’s edition editor), to Polish-Bulgarian political and cultural relations in the late 1930s and their local repercussions in Poznań and last but not least – to the language of the first edition and its translation and re-translation. The aim of the publication – to remind the first edition of the book, to make it accessible for Bulgarian readers and to restore the memory about its authors and editors – is thoroughly fulfilled. Moreover, an additional advantage of the book is that it makes its readers more aware of the difference in Bulgarians’ self-representational practices before and after the Second World War.